(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
This paper identifies the main factors affecting the implementation of e-learning in continuing education and on the lifelong learning general economy in Africa. The systematic in-depth literature review indicated e-learning adoption factors that could have impacts. This emerging framework is already offering a framework to assess the uneven and difficult implementation of e-learning in initial and continuing educational institutions in Africa, and this from both the perspective of learners and of instructors.